2019
DOI: 10.4038/cjs.v48i1.7592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different cooking methods on antioxidant properties of Tomato (<i>Lycopersicon</i> <i>esculentum</i>)

Abstract: Tomato (Lycopersicon esculentum) is one of the rich sources of antioxidants, mainly, lycopene which is known to be associated with decreased risks of chronic diseases. However, cooking influences the antioxidant properties of vegetables. Therefore, this study aimed to determine the effect of three cooking methods on the antioxidant properties of tomato. The conditions of the cooking methods of tomato were boiling at 100 ºC for 6 min, microwave cooking at 560W for 40 sec and stir-frying at 230 ºC for 4.5 min. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…In conclusion, the TPC in all the cooked samples showed a slightly lower value than in the raw sample in relation to dry matter. As the yield factor was around 0.50–0.56 some phenols must have been destroyed during the processing of the sofrito as observed somewhere else [16]. On the contrary, the other three antioxidant capacity methods showed higher values in cooked samples than in the raw one.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In conclusion, the TPC in all the cooked samples showed a slightly lower value than in the raw sample in relation to dry matter. As the yield factor was around 0.50–0.56 some phenols must have been destroyed during the processing of the sofrito as observed somewhere else [16]. On the contrary, the other three antioxidant capacity methods showed higher values in cooked samples than in the raw one.…”
Section: Resultsmentioning
confidence: 89%
“…For the studied samples, 90 min was selected as steady reaction time. Subsequently, all samples were measured after 90 min of incubation in the dark at room temperature (25 ± 2 ℃) with the DPPH radical at 517 nm using a spectrophotometer (Biomate-3, Thermospectronic, Mobile, AL, USA) [16].…”
Section: Methodsmentioning
confidence: 99%
“…Selain jenis teknik pemasakan, pengadukan merupakan salah satu faktor yang dapat mempengaruhi kelarutan suatu zat dalam pelarut (Sinala, 2016). Hal ini dibuktikan dalam penelitian Thanuja et al, (2019) bahwa adanya proses pengadukan pada saat menggoreng (menumis) dan merebus dapat menyebabkan turunnya kadar TPC (Total Phenolic Content) dan TFC (Total Flavonoid Content) pada tomat. Hasil penelitian tersebut juga diperkuat oleh penelitian Dewi (2010) yang menunjukkan bahwa lama pengadukan dapat meningkatkan kelarutan testosteron pada proses ekstraksi teripang pasir.…”
Section: Pendahuluanunclassified
“…
Tomatoes contain several health-promoting chemical compounds, including lycopene, α-carotene, beta-carotene, γ-carotene, phytoene, phytofluene, lutein and Vitamin C. 1,2 According to Evoli et al 3 heating process of tomatoes can increase the content of lycopene content in the extract and improve antioxidant activity of the extract. 3,4 Conversely, the content of beta-carotene, flavonoids and Vitamin C was found to decrease, and this indicated that the antioxidant activity of the extract must be due to the lycopene compounds. 2 Lycopene in tomatoes has been used as a nutraceutical to regulate blood lipid levels; hence, it has potential to prevent atherosclerosis.
…”
mentioning
confidence: 99%